THE IMPORTANCE OF CYTOKINES IN PERIODONTAL DISEASE AND RHEUMATOID ARTHRITIS. REVIEW - Maria Alexandra Martu; Sorina Mihaela Solomon; Vasilica Toma; George Alexandru Maftei; Alexandru Iovan; Andra Gamen; Loredana Hurjui; Elena Rezus; Liliana Foia; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2019)
Both rheumatoid arthritis (RA) and periodontitis (PD) are complex chronic inflammatory diseases who share a multitude of susceptibility factors (especially genetic and environmental risk factors). A important difference between these pathologies is that periodontal disease results from the inflammation that develops in response to the subgingival microbiota, while the inflammation in rheumatoid arthritis stems from an exaggerated specific adaptive autoimmune response. This proinflammatory status is perpetuated by the continued bacterial challenge in periodontitis and the autoimmune response triggered in RA, culminating in the progressive destruction of tissues that eventually lead to the signs and symptoms of the disease. Despite the differences in mechanisms of etiological initiation, the idea of polymorphisms of genes that encode certain cytokines which results in connective tissue damage and bone metabolism alterations in the two pathologies mentioned is a bridge which links these diseases. Additionally, there is evidence that both periodontitis and RA are manifested as persistent levels of proinflammatory cytokines and associated molecules. In addition, therapeutic strategies based on blocking proinflammatory cytokines in RA have been shown to have an impact on the overall periodontal status. This review analyses the main molecules which have an impact in the development of both diseases and evaluates possible clinical implications and bidirectional relationships which influence the overall status of the patient.